Fidelity and loyalty on the radio: a view from listeners from Santa Catarina (Intercom - Brazilian Journal of Communication Sciences, 2023)
This research sought to understand the reasons that lead a person to privilege a given radio broadcaster among competitors and other media. As a general objective, we had to analyze the factors that motivate a listener to be loyal to a certain radio station. The present investigation is exploratory and of a descriptive nature with a qualitative approach, sampling by intentionality before the analysis criteria of this study. The data were collected through in-depth interviews with listeners considered loyal by the broadcasters through a semi-structured script with open questions. As an analysis technique, content analysis was used. The factors that motivated the loyalty of the research radio listener were programming, radio announcer, bond, interactivity, and habit.
Keywords: Radio; Audience; Fidelity; Loyalty; Brand equity